ANALISIS SUSUT ENERGI PADA SISTEM JARINGAN DISTRIBUSI DI PT. PLN APJ YOGYAKARTA UPJ WONOSARI UNIT SEMANU - Henrey Daniel Dalam (Seminar Nasional Informatika (SEMNASIF), 2013)
Energy losses of electrical distribution Engineering are important phenomenon in the determination of electrical tariff. Therefore, the energy losses of an electrical system should be really made as small as possible. The energy losses of PT. PLN APJ Yogyakarta UPJ Wonosari Semanu  are great enough. Why are the enough losses being so big? The existing energy losses of an area present the electrical condition in that area. Simple analysis will represent electrical system service in the condition of load the length of the electrical system and the energy loss, and then determine the electrical service quality to customers. Load capacity and losses condition, which happen in the electrical distribution should be paid  into attention, especially at peak load time, at  which the energy loss can be known. The length of 20 KV feeder in Semanu may be the main cause of the great losses. The result analysis should the energy losses was big enough at peak load time. The losses increased due to the raise in the length of feeder. The energy losses of 855,751 kwh happened for the length  of feeder of 32,94 km. While a length of line of 66,9 km made 1.616,970 kwh losses. The 61 ampere load has a relation to 1,172Kwh energy losses and the load at 221 ampere previded 129,673 kwh energy losses